An optimization model for operations of large scale hydro power plants - Alvarez, Gonzalo Exequiel (2020)
Globally, there is an increase in the proportion of renewable sources for electricity generation. Among renewable sources, hydropower is the most widespread. For this reason, the improvements of their applications have been the focus of researches. Hydroelectric power plants have numerous aspects which might represent several economic advantages, if they are operated efficiently. Mathematical optimization models are interesting tools that help in the decision-making processes. In this context, this paper introduces a new Mixed Integer Lineal Programming model that determines the most convenient combination of units to operate a large-scale hydro power plant. Several aspects of reality are taken into account, which are sometimes not considered, such as the variation of the hydraulic head and the performance of other elements besides the turbines, as floodgates. To prove the effectiveness of the new model, the Itaipú Power Plant is selected as a case study. It has an installed power capacity of 14,000 MW and holds the world record in terms of annual generation with 103 million MWh. Three possible scenarios are evaluated in order to analyze the behavior of this plant in normal and extreme situations. The results indicate that the model effectively reduces computational times, and that power generation is influenced by market price variations and reservoir limitations.